RESEARCH ON THE ROLE OF A LEADER IN ENSURING THE EFFICIENCY OF TEAM ACTIVITIES - LUHOVA, Viktoriia; MARTIYANOVA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the role of a leader in increasing the efficiency of team activities, the development of tools, and their testing at a domestic enterprise. The paper uses the method of document analysis (in particular, scientific publications by domestic and foreign researchers over the past 5 years) that highlights leadership; the questionnaire method is used to collect data on employees’ views on the leader and assess his influence on teamwork; the processing and analysis of the collected data were carried out using Excel tables. The article examines the essence of leadership, which is the ability to influence individuals and groups, directing their efforts to achieve the organization’s goals, that is, to ensure the effective interaction of group members. It is proven that the leader plays an important role in ensuring the team’s efficiency. Based on the analysis of scientific sources, key aspects of leadership were identified, namely the effectiveness of the leader’s performance of management functions: planning, organization, motivation, and control; the ability to ensure effective communication, a high level of trust and cohesion, the ability to provide a favorable socio-psychological climate and cultural support. Accordingly, a questionnaire was developed and conducted among employees to assess the leader’s influence on teamwork. The study results show that employees generally highly appreciate the leader’s ability to set goals, plan team activities, organize work, and motivate team members. The results also indicate a high level of leader competence in establishing communication ties and ensuring cohesion and cooperation. It has been proven that a leader positively impacts corporate culture and psychological climate, helps resolve conflicts, and increases the energy and confidence of the team. However, specific problems with the distribution of tasks and responsibilities require management’s attention. This article contributes to the understanding of the role of leadership in ensuring effective team performance, offering practical recommendations for improving leadership competence and optimizing management processes in the organization.